(3TQM NGJeI GdJUhas - (3eMeO GdjOGdj Hf GdeNJGQ Hf eMeO SYjO GdOjeGfj,J (B1164 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3jbhd GdabjQ Edi dWa QHg GdhLd ef SA cSHg hHYO abO cfG hVYfG YbjOI ai JhMjO GdYGeI Ydi WQjb GdeJcdejf Ke NJefGgG HNGJeI ai GdJUha GdPi gh JhMjO GdNGUI s
(3BNQgG (B:s
(3hgPG BNQ eG bUOfGg ef TQM gPg GdNGJeI hGdMeO ddg Ydi JeGeg s
(3HgG fXGe GdJYbjHIs
(3YdjgG eWGdYIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdeYgO GdehQjJGfi ddHMK GdYdei (B((3JUha (B1431) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs